Marriage Guidance Towards Family Resilience in Aceh: A Study of Islamic Law Philosophy - Saleh, Juwaini; Amri, Nurullah; Kamal, Mustafa; Abdullah, Afrizal; Mukhtar, Masrizal (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This paper aims to examine government policies related to marriage guidance in order to establish family resilience with an Islamic legal philosophy approach. This study used a philosophical approach to Islamic law. The data were collected through literature studies and in-depth interviews. The results of the study indicate that government policy has created a marriage guidance program to increase family resilience. The implementation of marriage guidance in Aceh still faces obstacles from the formulation of the implementation model, the preparation of operational standards, methods, techniques, materials, and time allocation, as well as synergies with other related agencies. Marriage guidance is not an absolute requirement for marriage. Both the provincial Ministry of Religion and the City Regency Ministry of Religion do not periodically evaluate the marriage guidance program. The budget from the government is still minimal, and the need for cooperation between institutions causes the implementation of marriage guidance not to run optimally. However, marriage guidance from the perspective of Islamic legal philosophy aims for the benefit of prospective husband and wife, their families and communities, and even the state, therefore, this program is quite essential. Moreover, it is associated with family resilience, meaning that marriage guidance will strongly influence family resilience.